Parkinson's Disease and Forced Exercise: A Preliminary Study. (19th June 2013) - Qutubuddin, Abu; Reis, Timothy; Alramadhani, Raed; Cifu, David X.; Towne, Alan; Carne, William
Abstract : Objective . The concept of forced exercise has drawn attention for the treatment of Parkinson's disease symptoms with anecdotal reports of success. This study sought to ascertain any significant effect of forced exercise using a motorized stationary bicycle when compared to controls on Parkinson's disease symptoms in a blinded, randomized, and controlled setting. Setting . Parkinson's disease outpatient clinic, Veterans Administration Medical Center. Method . We assessed 23 patients (13 experimental and 10 controls) on a number of standard Parkinson's measures at baseline, after participation in eight weeks of twice weekly forced exercise or eight weeks of conventional clinic care, and then after a three-month period had elapsed. Dependent measures were UPDRS-III, Berg Balance Scale, finger taping test, and the PDQ-39. Results . Results did not demonstrate any main effect differences between the exercise and control groups on any measure at any point in time. A within subjects effect was demonstrated for the forced exercise group on overall UPDRS-III scores at the three-month end point. No other within group effects were noted. Results suggest that early enthusiasm for forced exercise may need tempering. Limitations of the study are discussed as well as numerous logistical challenges to this type of study.